Impact of periodontal maintenance on tooth survival in patients with removable partial dentures. (26th December 2014) - Tada, Sayaka; Allen, Patrick Finbarr; Ikebe, Kazunori; Matsuda, Ken‐ichi; Maeda, Yoshinobu
Abstract Aim Removable partial dentures (RPDs) may have a negative impact on oral health and have the potential to cause further tooth loss, especially of abutment teeth. However, no evidence indicates the effective interval of regular periodontal maintenance after RPD provision. This practice‐based cohort study aimed to examine the impact of regular periodontal maintenance visits on survival of RPD abutment teeth. Materials and Methods One hundred and ninety‐two patients had been previously provided with 304 new clasp‐retained RPDs at Osaka University Dental Hospital, Japan. Using the Kaplan–Meier method and log‐rank test, 1094 abutments were analysed to illustrate survival curves and to compare each curve. According to the frequency of periodontal maintenance, study samples were divided into three groups; every 3–6 months (3–6M) group, 1‐year (1Y) group and no‐maintenance (NM) group. Results Seven‐year cumulative survival rates were 83.7% (3–6M), 75.5% (1Y) and 71.9% (NM) respectively. Survival of abutment teeth in the 3–6M group was significantly better than both 1Y (p = 0.005) and NM (p < 0.001) groups. Conclusion These longitudinal clinical data indicates that periodontal maintenance at least once in 6 months had the most favourable outcome. Frequent periodontal maintenance after RPD provision could be effective in preventing further tooth loss.